GCTE : a national graduate certificate in tertiary education : final report 2009. - Vale, Deborah; Tynan, Belinda; Smyth, Robyn; McCormack, Coralie; Fisher, Marilyn; Zeegers, Margaret; Sparrow, Heather (Australian Learning and Teaching Council, 2009)
The GCTE project group aimed to devise a means of delivering the best possible Graduate Certificate in Tertiary Education for new academic staff, creating viable cohorts, and increasing the number of students in each aspect of the program, through a collaborative GCTE across five universities. This report details the road travelled by the project partners over the two years of the project. Part one describes the vision of the project leaders in 2007. Section two describes the project methodology. Section three reviews the literature around graduate certificates in general and Section four discusses the successes, achievements, challenges, and recommendations of the project partners.